Firm size and earnings management: Unlocking the strategy of upward or downward earnings? - Mohamed, Zuraina Sal Salbila; Kamarudin, Siti Nurhazwani; Ahmad, Mahyudin (International Journal of Accounting, Finance and Business, 2025)
Previous empirical studies on earnings management have often found conflicting findings regarding factors that contribute to such practice. They also found that the practice of earnings management has been abused by manipulating accounting figures and taking advantage of the relaxation of accounting rules. This study examined the effects of firm size on earnings management practices among Malaysian public listed firms. Secondary data from 2014 to 2021 obtained from DataStream and the Annual Reports of 492 firms, were analysed using Fixed Effects Estimation methodology. Findings indicate that larger firms often have a higher tendency to engage in earnings management, especially downward earnings management. This lends evidence of the Political Costs Theory and Political Power Theory underlying the earnings management practice among large, listed firms in Malaysia. The findings have a significant implication on regulatory bodies, such as the Securities Commission, which has to tighten accounting rules and increase oversight among large, listed firms. This measure can reduce the manipulation of financial reports by managers who take advantage of regulatory weaknesses to achieve their opportunistic objectives.